Research in labor economics. Vol. 33 - Polachek, S. W.; Tatsiramos, Konstantinos; Akee, Randall K. Q.; Edmonds, Eric V., 1971- (Research in labor economics., 2011)
This volume contains nine original innovative chapters on worker well-being. Three chapters are on time allocated to work and human capital acquisition, three on aspects of risk in the earnings process, two on migration, and finally one on how tax policies affect poverty. Questions answered include: Are more educated women now opting out of work with a higher probability than in the past? Under what circumstances do young adults allocate non-school time to educational pursuits? How do macroeconomic shocks affect labor force participation rates? Can tax policies alleviate poverty? Are workers compensated adequately for taking risks? Do differences in private and public sector earnings affect mobility between the two sectors? And, do migrant parents affect educational decisions of their offspring?.